Pemodelan dan Perbaikan Proses Bisnis Pemenuhan Pesanan Kopi dengan Metode Business Process Management (Studi Kasus Bawadi Coffee) - Nur Izzaty; Elviza Masyurah; Hasan Yudie Sastra; Sri Rahmawati (Industrika : Jurnal Ilmiah Teknik Industri, 2023)
Coffee is one of Indonesia’s leading commodities which has enormous demand both from domestic and global market. The increasing number of requests makes suppliers and producers of coffee-based products not always able to fulfil the demands due to non-standard and inflexible business processes. This study examined the coffee demand fulfilment business process at SME BC, a producer of Gayo Arabica coffee powder, employing the Business Process Management (BPM). The business process modelling was conducted using Business Process Model and Notation (BPMN) and the simulation with Software Bizagi Modeler. The as-is model resulted in 37 activities with total time of 1,165 minutes, while the proposed to-be model resulted in 33 activities with total time of 183 minutes. The comparison with Devil’s Quadrangle, time-wise and flexibility-wise, between the as-is and to-be model indicated increases in time efficiency of 84% and process flexibility by 11%. Keywords: BPMN, Business Process Management, Devil’s quadrangle, Value added analysis